Musyarakah dalam Kerangka ESG dan Maqashid al-Shariah: Strategi Keuangan Syariah untuk Mendukung Tujuan Pembangunan Berkelanjutan (SDGs) - Adawiah, Amalia Muazzah; Muhammad Azkia Fahmi; Irfan Anshori (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
The sharia financial industry is in the main spotlight in economic development based on Islamic principles. One of the financial instruments that is widely used in this industry is musyarakah, which is a form of mixing contract. The concept of syirkah or partnership in Islam has a strong legal basis and is regulated in detail in sharia law. Therefore, the aim of this article is to conduct an in-depth analysis of mixed contracts in musyarakah, including the concept of syirkah, its types, and its implementation in the sharia financial industry. First of all, to understand the mixed contract in musyarakah, we need to explore the concept of syirkah itself. The research methodology used in this research is a qualitative method with a literature study or study research approach. In conclusion, the analysis of mixed contracts in musyarakah is one form of cooperation contract that is important in the sharia financial industry. Through an in-depth understanding of the concept of syirkah and its various types, it can be concluded that musyarakah has unique characteristics that differentiate it from other cooperation contracts. One of the advantages of musyarakah is the principle of fair distribution of risks and profits between the parties involved. This illustrates the essence of the principles of justice and togetherness in Islam, which are the main foundations in sharia financial practices.